NALAR PANCASILADALAM KOMUNIKASI POLITIK (Lembaga Penerbitan Universitas Esa Unggul, 2016)
AbstractThis paper discusses the philosophical-theoretical three significant issues related to the existence of political communicates, namely the nature of political communication, political communication principles, and reason Pancasila in political communication. Reason is Pancasila is the embodiment of the values of Pancasila as the foundation of ethics in political communication. So that political communication is no longer used only as a tool to achieve political purposes, but should be submissive to the interests and ideals of the nation and the country as stated in the Preamble to the Constitution of 1945. Reasoning first principle of Pancasila politics in the context of political communication is to provide a theological foundation that political communication that is built to be in harmony with the values of divinity. The second reason Pancasila in political communication, namely that political communication should be conducted in a fair and uphold the values kemanusiaam. The third reason Pancasila in political communication is political communication are built and made to be oriented in maintaining the unity and integrity. The fourth reason in political communication contains Pancasila philosophy that any differences in political communication is a natural thing, but it must be remembered that the distinction should be guided by wisdom (wisdom) within the scope of deliberations. Reason fifth of Pancasila in political communication implies that political communication is done must uphold the values of justice regardless of their origins. Keywords: Pancasila values, political communication, the nature and principles of political communication. AbstrakTulisan ini membahas secara filosofis-teoretistiga persoalan penting yang terkait dengan eksistensi komuniksi politik, yaitu hakikat komunikasi politik, prinsip-prinsip komunikasi politik, dan nalar Pancasila dalamkomunikasi politik.Nalar Pancasila yang dimaksud adalah pengejawantahan nilai-nilai Pancasila sebagai landasan etik dalam melakukan komunikasi politik.Sehingga komunikasi politik tidak lagi dijadikan hanya sebagai alat untuk meraih kepentingan politik, tetapi harus berkhidmat kepada kepentingan dan cita-cita bangsa dan negara sebagaimana tercantum dalam Pembukaan Undang-Undang Dasar 1945.Nalar politik sila pertama Pancasila dalam konteks komunikasi politik adalah memberikan landasan teologis bahwa komunikasi politik yang dibangun harus selaras dengan nilai-nilai ketuhanan.Nalar kedua Pancasila dalam komunikasi politik, yaitu bahwa komunikasi politik harus dilakukan secara adil dan menjunjung tinggi nilai-nilai kemanusiaam.Nalar ketiga Pancasila dalam komunikasi politik adalah komunikasi politik yang dibangun dan dilakukan harus diorientasikan dalam menjaga persatuan dan kesatuan. Nalar keempat Pancasila dalam komunikasi politik mengandung filosofi bahwa setiap perbedaan dalam komunikasi politik adalah hal yang wajar, namun harus diingat bahwa perbedaan itu harus dilandasi oleh kebijaksanaan (wisdom) dalam lingkup musyawarah. Nalar kelima dari Pancasila dalam komunikasi politik mengandung pengertian bahwa komunikasi politik yang dilakukan harus menjunjung tinggi nilai-nilai keadilan tanpa membedakan asal-usul mereka. Kata kunci: nalar Pancasila, komunikasi politik,hakikat dan prinsip-prinsip komunikasi politik.